Application of discrete wavelet transformation in damage detection. Part II: Heat transfer experiments - Ziopaja, Krzysztof; Pozorski, Zbigniew; Garstecki, Andrzej (Computer Assisted Methods in Engineering and Science; Vol 13 No 1 (2006), 2022)
A non-destructive method of damage detection based on heat transfer experiments and 2-D Discrete Wavelet Transform (DWT) is discussed. In this paper real experiments with the use of thermography measurement techniques are substituted by numerically simulated experiments. The plates were modelled as 2-D and 3-D structures. Two kinds of structures are considered: homogeneous in undamaged state and non-homogenous. Measurement errors are accounted for by introduction of a white noise. The efficiency of the method is demonstrated by the way of numerous examples.